The Weekend Drug; Recreational Use of Sildenafil Citrate and Concomitant Factors: A Cross-Sectional Study - Atsbeha, Berhanemeskel Weldegerima; Kebede, Beza Tefera; Birhanu, Biruktawit Shewafera; Yimenu, Dawit Kumilachew; Belay, Wudneh Simegn; Demeke, Chilot Abiyu (Frontiers in Medicine, 2021)
Background: Men who use erectile dysfunction medications for recreational purposes may be at increased risk of becoming psychologically dependent, which in turn could lead to psychogenic-based erectile dysfunction symptoms. Sildenafil has become one of the most commonly prescribed and abused drugs available today. Objectives: This study aimed to describe the utilization pattern and associated factors of sildenafil citrate among its users visiting community pharmacies in Gondar, Ethiopia. Methods: A cross-sectional study was conducted. A self-administered, structured questionnaire was used for data collection, and Statistical Package for Social Sciences (SPSS) version 20 was used for data analysis. A regression analysis was conducted to determine the association between study variables, and a P-value of less than 0.05 was considered to declare statistical significance. Results: A total of 65 men participated in the study. From the total study participants, 58.5% were aged 22-37 years and about 40% of them had multiple partners. Among the total study participants, 66% of them reported that they use sildenafil for recreational purposes. The use of sildenafil for recreational purposes 43 (66.2%) was found to be higher than its use for medical purposes 22 (33.8). Furthermore, the duration of sildenafil use was found to be significantly associated with its use for recreational purposes. Non-recreational users of sildenafil include patients with diabetes mellitus (27.1%), heart disease (9.2%), hyperlipidemia (4.2%), and relationship problems due to stress and poor communication (3.1%). Conclusion: The prevalence of sildenafil use for recreational purposes was higher. There should be a collaborative effort among pharmacists, health professionals, and policymakers to improve the rational use of sildenafil and other phosphodiesterase-5 inhibitors (PDE5Is).